1992
DOI: 10.1192/bjp.161.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors, Arousal and Schizophrenic Relapse

Abstract: This annotation describes psychophysiological research that has examined the hypothesis that autonomic hyperarousal is a possible mediating factor between schizophrenic relapse and psychosocial influences such as expressed emotion (EE) and life events. We review several studies that have measured psychophysiological activity in schizophrenic patients while in the presence of their relatives. The findings from this area of research are compared with those of other psychophysiological studies of schizophrenia wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 51 publications
4
31
0
2
Order By: Relevance
“…The activation of implicational meaning structures derived from previous experiences of psychosis will initiate the process of relapse. A primary source of information for a relapse configuration is internal information on body state and arousal (Tarrier and Turpin, 1992), and cognitiveperceptual change (Neuchterlein and Dawson, 1984;Frith, 1992). Indeed, feelings of lack of control over cognitive and perceptual processes during relapse have been reported by a number of authors (Bowers, 1968;Freedman and Chapman, 1973;Donlan and Blacker, 1975).…”
Section: Initiation Of Relapsementioning
confidence: 97%
“…The activation of implicational meaning structures derived from previous experiences of psychosis will initiate the process of relapse. A primary source of information for a relapse configuration is internal information on body state and arousal (Tarrier and Turpin, 1992), and cognitiveperceptual change (Neuchterlein and Dawson, 1984;Frith, 1992). Indeed, feelings of lack of control over cognitive and perceptual processes during relapse have been reported by a number of authors (Bowers, 1968;Freedman and Chapman, 1973;Donlan and Blacker, 1975).…”
Section: Initiation Of Relapsementioning
confidence: 97%
“…Additional research is required to answer this question. In the context of research on expressed emotion and psychophysiological arousal, Tarrier and Turpin (1992) summarize data indicating that negative relationships with a significant other may heighten arousal. Presuming this arousal is negative to the patient, we would expect these physiological responses would, in turn, exacerbate patients' symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from studies on schizophrenic clients (reviewed by Tarrier & Turpin, 1992) and children with obsessive-compulsive disorder indicate that clients living in high EE families demonstrate higher levels of physiological arousal than those with low EE relatives. At times this finding is obtained only when arousal is measured while the relative is present; in other research, this higher arousal was observed with and without the relative's physical presence.…”
Section: How Does Ee Lead To Relapse?mentioning
confidence: 94%